Patent trend and competitive analysis of cancer immunotherapy in the United States. Issue 11 (2nd November 2017) - Pan, Chia-Lin; Chen, Feng-Chi
ABSTRACT: Immunotherapy has brought high hopes for cancer treatment, and attracted tremendous resources from the biopharmaceutical community. Here we analyze cancer immunotherapy-related patents granted by the United States Patent and Trademark Office in the past decade (2006–2016). A total of 2, 229 patents were identified in 13 subfields. The growth of patent number in this field has outpaced the background rate, with cytokine-related therapies, immune checkpoint inhibitors, and natural killer cell therapies growing the most rapidly. The top 15 assignees possess 27.6% (616) of the patents. Amgen is the largest patent holder, followed by Novartis, and then by Chugai Seiyaku. The top assignees have focused on different subfields, and collaborated with each other for technology development. Our competitive analysis reveals that Novartis, Chugai Seiyaku, and Abbvie lead in both patent number and average quality of patents. Meanwhile, Immunomedics owns a high-quality though relatively small patent portfolio in single-chain variable fragment technology, which is not the focus of the abovementioned forerunners. Overall, our analysis illustrates an ecosystem where industry giants and smaller-size players each occupies a niche. Selection and succession are expected to continue for years in this young ecosystem.